Acute effects of different durations of static stretching on the eccentric strength and power of leg flexor muscles - Krcmar, M.; Xaverova, Z.; Lehnert, M.; Krcmarova, B.; Šimonek, J.; Kanásová, J.; Bognar, G.; Vanderka, M.; Ruiz-Pérez, I.; Ayala, F. (Isokinetics and Exercise Science, 2018)
Research suggests that effect of continuous static stretching on sport performance and/or injury prevention depends on the total stretching volume. OBJECTIVE: To analyze the acute effects of three short duration static stretching interventions of four lower limb muscle groups (15, 30 and 60 seconds per muscle) on the eccentric isokinetic peak force (PF) and peak power (PP) measures obtained during leg press exercise. METHODS: A total of thirteen amateur athletes, 7 men and 6 women, completed four different interventions in a randomized order on separate days: one control (non-stretching) and three static stretching (SS) interventions (1 × 15 s, 1 × 30 s and 1 × 60-s). After the stretching or control interventions, eccentric isokinetic PF and PP were assessed at two different linear velocities (200 mm/s and 400 mm/s). RESULTS: Measures were compared via a magnitude-based inference analysis. The results of this study showed no significant main effects between intervention-paired comparisons for any PF and PP measures. CONCLUSION: The findings of this study suggest that sport-relevant durations of SS have no effect on eccentric strength and power performance during leg press exercise and hence, the role of SS as a method to reduce the relative risk of injury is questionable